2014
DOI: 10.1371/journal.pone.0105423
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Retardation and Lack of Hypotaurine in Ezrin Knockout Mice

Abstract: Ezrin is a membrane-associated cytoplasmic protein that serves to link cell-membrane proteins with the actin-based cytoskeleton, and also plays a role in regulation of the functional activities of some transmembrane proteins. It is expressed in placental trophoblasts. We hypothesized that placental ezrin is involved in the supply of nutrients from mother to fetus, thereby influencing fetal growth. The aim of this study was firstly to clarify the effect of ezrin on fetal growth and secondly to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Over the years, different target proteins such as ezrin 61 , IQGAP1 74 , non-muscle myosin IIA 23 or proteins related to the tissue plasminogen activator pathway 75 have been shown to act as S100P binding partners in normal and cancer cells where they are believed to regulate motility and invasion. Interestingly, ezrin knockdown has been shown to play key roles during gestation leading to foetal growth retardation 76 , whilst non-muscle myosin IIA is essential during embryogenesis and placentation 77 and may regulate cellular motility of trophoblasts in culture 78 . However, a role for IQGAP1 and tissue plasminogen activator in trophoblast motility/invasion are yet to be characterised, but both have been shown to be key regulators of cancer motility/invasion 79 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, different target proteins such as ezrin 61 , IQGAP1 74 , non-muscle myosin IIA 23 or proteins related to the tissue plasminogen activator pathway 75 have been shown to act as S100P binding partners in normal and cancer cells where they are believed to regulate motility and invasion. Interestingly, ezrin knockdown has been shown to play key roles during gestation leading to foetal growth retardation 76 , whilst non-muscle myosin IIA is essential during embryogenesis and placentation 77 and may regulate cellular motility of trophoblasts in culture 78 . However, a role for IQGAP1 and tissue plasminogen activator in trophoblast motility/invasion are yet to be characterised, but both have been shown to be key regulators of cancer motility/invasion 79 81 .…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties of hypotaurine have been repeatedly demonstrated to elicit protective effects against stress-induced cytotoxicity in several contexts ( Fellman and Roth, 1985 ; Aruoma et al, 1988 ; Green et al, 1991 ; Fontana et al, 2004 ; Fontana et al, 2008 ). Hypotaurine was shown to protect against oxidative stress in rat placental trophoblasts, while knockout of the gene coding for ezrin, a membrane-cytoskeletal protein necessary for hypotaurine transport, resulted in depleted fetal plasma hypotaurine and reduced fetal weights of knockout embryos ( Nishimura et al, 2014 ; Nishimura et al, 2015 ). Hypotaurine was also shown to elicit hepatoprotective effects in a rat model of ischemic injury through its antioxidative conversion to taurine ( Sakuragawa et al, 2010 ), and taurine (the downstream product of hypotaurine) was recently shown to reduced hepatic injury in mice after VPA exposure ( Khodayar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, L-carnitine has a half-life ranging from 2 to 15 h ( Goa and Brogden, 1987 ), and to our knowledge, there is no data available for mice. Hypotaurine is transported across the plasma membrane in cultured rat syncitiotrophoblast cells, and fetal levels of hypotaurine rely on placental hypotaurine transport ( Nishimura et al, 2014 ; Nishimura et al, 2015 ). Transport of CoA is less studied and poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the remaining CE–MS‐based metabolomics applications of the past two years can be found in Table .…”
Section: Applicationsmentioning
confidence: 99%